EVOLUTION AND EARLY FORMS OF FOLK PROVERBS IN ANCIENT TURKS STONE INSCRIPTIONS - Rahmatov Yoldosh Gaybullaevich (Scholar Express Journal, 2024)
The genre of proverb is one of the fundamental bases of oral folklore. The emergence, formation and development of proverbs are directly related to the history, worldview, contemplation, spirituality of the nation. As the encyclopedic scientist Abdurauf Fitrat said: ... the proverb occupies a special place among the examples of oral creativity written for the understanding, pleasure, feeling, spirit of many people. Since no other genre can compare with the proverb either in quantity or in application. If the constant use of proverbs in our living language in accordance with the requirements of speech, as well as continuous development and expansion in terms of meaning is the first reason for the steady increase in the layers of such thinking, then the use of these samples by poets and writers in their works is the second factor that ensures the viability and stability of the genre
Keywords: second; proverbs; application